A D-band transceiver front-end for broadband applications in a 0.35μm SiGe bipolar technology - Chakraborty, Abhiram; Trotta, Saverio; Wuertele, Johann; Weigel, Robert (Radio Frequency Integrated Circuits Symposium, 2014 IEEE, 2014)

A low-phase-noise monolithically integrated 60 GHz push-push VCO for 122 applications in a SiGe Bipolar technology - Chakraborty, Abhiram; Trotta, Saverio; Weigel, Robert (IEEE Bipolar/BiCMOS Circuits and Technology Meeting (BCTM), 2013)
elib2cris::1512001600,chakraborty2013

A low-power, low-noise, highly-linear receiver for 122 GHz applications in a SiGe BiCMOS technology - Chakraborty, Abhiram; Trotta, Saverio; Aufinger, Klaus; Lachner, Rudolf; Weigel, Robert (IEEE Radio and Wireless Symposium (RWW), 2014)
elib2cris::1512001600,chakraborty2014

Design of Gain Optimized Broadband Low Noise Amplifiers at 120 GHz using SiGe Technology - Chakraborty, Abhiram; Kissinger, Dietmar; Lämmle, Benjamin; Hartnagel, Hans; Weigel, Robert (German Microwave Conference, 2010)
This paper presents the design of single-ended, double stage cascode low noise amplifiers at 120 GHz. A design methodology employing three techniques for gain enhancement of the LNA is presented. The effect of traditional emitter - degeneration technique and its feasibility for simultaneous noise and power matching is evaluated at 120 GHz. The LNAs are designed in a 250 GHz fT and 300 GHz fmax 0.13 μm SiGe:C BiCMOS process. By employing the three design techniques the gain of the LNA is improved by almost 3.5 dB. The two stage gain optimized LNA achieves a gain of 24 dB and a noise figure of 7.2 dB. The circuit works with a supply voltage of 3.3 V and consumes less than 40 mW of power.
elib2cris::1512001600,chakraborty2010
Keywords: BiCMOS integrated circuits; Broadband amplifiers; Low-noise amplifiers; Noise figure; wideband amplifiers; cascode low noise amplifier; emitter-degeneration technique; 120 GHz; 250 GHz; 300 GHz; noise matching; SiGe Heterojunction Bipolar Transistor

Design Techniques for Broadband Low Noise Amplifiers at 120GHz in a SiGe BiCMOS Process - Chakraborty, Abhiram; Lämmle, Benjamin; Kissinger, Dietmar (ANALOG'11 Fachtagung Entwicklung von Analogschaltungen mit CAE-Methoden, 2011)
elib2cris::1512001600,chakraborty2011